Kriteria Kafā’ah antara Pelaku dan Korban dalam Hukuman Kisas (Studi Komparasi Pendapat Mazhab Syafii dan Hanafi) - Yogi Achmad; Ayyub Subandi; Sirajuddin Sirajuddin (AL-QIBLAH: Jurnal Studi Islam dan Bahasa Arab, 2023)
This study aims to determine the views of the Shafi'i and Hanafi schools of thought on the criteria of kafā'ah in kisas punishment and to find out the similarities and differences of these two schools on this issue. The type of research used is descriptive qualitative research, which focuses on the study of manuscripts and texts. By using a normative juridical approach and supported by a comparative approach. From the results of this study it was found that the Shafi'i school views the differences between killers and victims in the aspects of belief and freedom causing kisas punishment to be given to the murderer who is more important in degree than the victim and not vice versa. murderer. As for the Hanafi school of thought, the difference between the killer and the victim in the aspects of belief, freedom, gender, and number does not invalidate the kisas law on the perpetrator. In general, these two schools of thought agree that differences in the gender aspect and the large number of killers from victims do not abort kisas punishment for murderers, and differ in views on differences in perpetrators and victims in the aspects of faith and freedom.